Left-sided thoracoscopy in the prone position for surgery of distal esophageal benign pathologies - (:unkn) unknown (My University, 2014)
Exposure of the distal esophagus can be achieved by a wide variety of surgical approaches. The standard procedure is mostly by laparoscopy. In cases where laparoscopy is relatively contraindicated, thoracoscopy is preferred. In this case, exposure of the distal esophagus from the aorta, heart and lung is technically challenging using thoracoscopy in the right lateral decubitus position. Surgery in the prone position for esophageal cancer has been successfully described in previous literature. We present our experience with left-sided thoracoscopy in the prone position in three patients with benign distal esophageal pathologies. This approach provided a much better exposure of the distal esophagus and enabled a successful surgery to be done in all patients with less manipulation of the lung.
Keywords: Thoracoscopy; benign pathologies; esophagus; prone position